2008
DOI: 10.1002/hed.20719
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence investigations to classify malignant laryngeal lesions in vivo

Abstract: There are differences in the in vivo tissue fluorescence between tissue with different gradings of dysplasia and carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 38 publications
0
17
0
2
Order By: Relevance
“…This difference in autofluorescence can be detected by inspecting the mucosa with a specialized endoscope (see Figure 2); or, alternatively, the difference in fluorescence can be quantified by splitting each reflected light into its constituent wavelengths and plotting intensity at each wavelength. 10 Several studies have demonstrated that autofluorescence endoscopy and spectroscopy are better at identifying invasive carcinoma when compared with microlaryngoscopy alone, 5,10-15 and many head and neck oncology centers use autofluorescence as an adjunct to microlaryngoscopic examination. There are, however, several limitations to autofluorescence examination.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This difference in autofluorescence can be detected by inspecting the mucosa with a specialized endoscope (see Figure 2); or, alternatively, the difference in fluorescence can be quantified by splitting each reflected light into its constituent wavelengths and plotting intensity at each wavelength. 10 Several studies have demonstrated that autofluorescence endoscopy and spectroscopy are better at identifying invasive carcinoma when compared with microlaryngoscopy alone, 5,10-15 and many head and neck oncology centers use autofluorescence as an adjunct to microlaryngoscopic examination. There are, however, several limitations to autofluorescence examination.…”
Section: Methodsmentioning
confidence: 99%
“…[19][20][21] Furthermore, ALA-induced fluorescence may be better than autofluorescence at distinguishing recurrent cancer from scar tissue following laser surgery. 21 Recently, however, Rydell et al 10 reported that the addition of ALA-induced fluorescence spectroscopy to autofluorescence examination did not further improve diagnostic accuracy. 10 As would be expected, ALA-induced fluorescence examination shares many of the limitations of autofluorescence described earlier.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…51,57,58 However, the addition of ALA-induced fluorescence to AF does not improve diagnostic accuracy. 59 ALA-induced fluorescence may also be better than AF in differentiating recurrent cancer from scar tissue after laser surgery. 51 Like AF, ALA-induced fluorescence cannot be used to determine histologic detail and thus cannot characterize grade of dysplasia or identify invasive carcinoma.…”
Section: Autofluorescencementioning
confidence: 96%
“…ir 100 proc. (25). Geri rezultatai aprašomi ir neurochirurgų: FD padeda tiksliau nustatyti galvos smegenų naviko ribas ir atlikti radikalesnę operaciją (26,27).…”
Section: Rezultatų Aptarimasunclassified